IMMUNOHISTOCHEMICAL EXPRESSION OF CD44 IN PATIENTS WITH HEPATOCELLULAR CARCINOMA - Nikolova, Dafina; Ivanova, Viktorija Chaloska; Jovanovic, Rubens; Janevska, Vesna; Trpcevska, Emilija Nikolovska; Nikolovska, Ance Volkanovska (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Introduction : CD44, a transmembrane glycoprotein with a role in cell-cell and cell-matrix interactions and one of the stem cell markers, is considered to participate in progression and prognosis of hepatocellular carcinoma (HCC), which makes it a potential prognostic marker and therapeutic target. We aimed to evaluate immunoexpression of CD44 in tumor and surrounding non-tumor liver tissue and to correlate it to multiple clinicopathological data in order to determine its prognostic value in patients from the Republic of North Macedonia. Material and Methods : Presence of the immunosignal and the percentage of CD44+ tumor cells at the whole tumor tissue sample and adjacent cirrhotic liver tissue were semi-quantitatively determined.The immunohistochemistry results were correlated to B and C hepatitis, tumor dimensions, enlarged lymph nodes, T status, differentiation (G), microvascular invasion, and survival. Results : We found a significant difference in CD44 expression between tumor and non-tumor liver tissue (p < 0.000) and significantly higher CD44 expression was also found in T4 tumors in comparison with T1 tumors (p < 0.01). Conclusion :  Expression of CD44 was significantly higher in tumor in comparison to non-tumor tissue and was significantly associated to T4 local tumor growth, making it a potential prognostic marker and therapeutic target. Keywords : CD44, HCC, immunohistochemistry, T status, survival